Al_Rahadenah in the markets of Morocco and Andalusia (7-9 AH / 13-15 AD) (Journal of Human Sciences, 2022)
The trade in the Islamic Morocco and Andalusia in the Middle Ages ‎‎witnessed a great boom, accompanied by the emergence of classes and   ‎‎types of merchants, most of whom knew and some of them ‎‎disappeared, or they changed with the succession of years, perhaps ‎‎verbally, but it remained a feature and form, and among those fees, a ‎‎kind of trade was adopted to sell old worn clothes, utensils, furniture, ‎‎and so on, and the owners of those professions took the title ‎‎‎(Al_Rahadenah), It is a name that some neglected its meaning and ‎‎purpose for reasons, the most important of which is the lack of a study ‎‎directed towards (Al_Rahadenah) as a category of merchants the origin ‎‎of their name and the type of their trade. ‎This research is an introductory study to reveal the meaning name ‎of ‎‎(Al_rahdanah) and to clarify the characteristics of (Al_Rahadenah) ‎‎trade, some aspects of their activity, and the follow-up of this trading ‎‎system in some of its stages in the markets of the Islamic Maghreb and ‎‎Andalusia in the Middle Ages‏.‏